The Sustainability of Pervasive Learning in Accounting Education: Strategy in the Transition of “Merdeka Belajar-Kampus Merdeka” - Diyah Probowulan (Jurnal Akuntansi dan Keuangan, 2022)
In accounting, sustainability can improve the accuracy, reliability, and relevancy of teaching and learning in the educational, economic, and social landscapes that are constantly changing and evolving towards Big Data Personalized Learning or Pervasive Learning. Firstly, the purpose of this paper is to provide a brief overview of the educational landscape in the accounting field in the context of pervasive learning during the transitional period of MBKM. Second, providing evidence of the new teaching and learning readiness of the 2020 MBKM grant recipients in the accounting education program at Muhammadiyah Higher Education. A literature study is conducted to support the empirical evidence obtained from questionnaires filled out by groups of Accounting Department students. This study finds that, although the beginning of pervasive learning is new for them, with the help of the technological convenience provided by the Ministry of Education and Culture's big data, it can be well-adopted. This convenience is due to the literacy approach that is used in disseminating information to students and the grant outcomes that must be implemented to create a conducive environment for teaching and learning. This research also finds that students' understanding of the use of learning technology has increased. The implications of these findings can provide the roadmaps and strategies that can be carried out in the accounting learning process in the MBKM era through pervasive learning and sustainable technology developments.